2020
DOI: 10.1007/s11192-020-03657-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge structure transition in library and information science: topic modeling and visualization

Abstract: The purpose of this research is to identify topics in library and information science (LIS) using latent Dirichlet allocation (LDA) and to visualize the knowledge structure of the field as consisting of specific topics and its transition from 2000–2002 to 2015–2017. The full text of 1648 research articles from five peer-reviewed representative LIS journals in these two periods was analyzed by using LDA. A total of 30 topics in each period were labeled based on the frequency of terms and the contents of the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Miyata et al (2020) applied Latent Dirichlet Allocation to identify LIS topics. They analyzed full texts of articles in five LIS journals in 2000–2002 and 2015–2017.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miyata et al (2020) applied Latent Dirichlet Allocation to identify LIS topics. They analyzed full texts of articles in five LIS journals in 2000–2002 and 2015–2017.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Content analysis was a strategy used to ascertain and classify research theme/topic embarked by postgraduate students. In LIS, similar studies to examine trends of research based on content analysis were conducted by (Armann-Keown & Patterson, 2020;Miyata et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Zong et al, (2013) conducted a study in China using postgraduate dissertations from 1994 to 2011 and found ontology, semantic web, electronic government, knowledge management and digital library were highly researched topics while research on cataloguing, digital library and knowledge organization were least researched. Miyata et al, (2020) conducted a study to identify LIS topics from 2000-2002 and 2015-2017. The study shows the internet influenced changes in LIS research. Song et al, (2020) revealed a change from traditional to digital library and research focus on data science.…”
Section: Literature Reviewmentioning
confidence: 99%
“…LDAvis (Sievert & Shirley, 2014), a web-based interactive visualization tool for qualitative assessment of topic models, enables an intuitive, yet profound, inspection of topic-term relationships in an LDA model (Miyata et al, 2020). The tool represents the inter-topic similarity as the distance between the topics, which is by calculating inter-topic Jensen-Shannon divergence (JS divergence) values.…”
Section: Research Papermentioning
confidence: 99%